CONSUMER MOTIVATIONS, ATTITUDE AND BEHAVIORAL INTENTION TOWARD GREEN HOTEL SELECTION - Wang, Lei; Wang, Zi-Xu; Wong, Philip Pong Weng; Zhang, Qi (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2021)
Most prior studies have investigated the relationship between green purchase attitude and behavior based on the Theory of Planned Behavior (TPB). However, TPB is a behavioral theory based on a causal process, and thus ignores consumers’ motivational aspects. The purpose of this study is to examine consumers’ motivational variables, in which monetary, convenience (location), hedonic and virtual motivation (social media) influence consumers’ intentions to visit green hotels based on generational characteristics. A survey questionnaire was developed where a total of 775 questionnaires were ultimately collected followed by subsequent empirical testing of the postulated hypotheses using SPSS and Structural Equation Modelling. The results suggest monetary and virtual motivation positively influence green purchase attitude (GPA) respectively, while convenience negatively influence GPA. GPA displays a positive influence on green purchase intention (GPI) while hedonic motivation plays no role in this study. In addition, statistically significant differences in monetary, convenience, hedonic, virtual motivation and GPI were observed between generations of consumers towards green hotel selection. The theoretical and practical implications of the results were highlighted, including limitations of the research. Lastly, this study addressed the relationship between motivational traits and behavioral intention in the hospitality and tourism field, and its results will provide useful information for green hotels’ stakeholders.